Eksplorasi Kepercayaan Orang Niniwe kepada Allah Ditinjau dari Yunus 3:1-10 - Elen, Maria; Ziliwu, Alnodus Jamsenjos Indirwan (Sekolah Tinggi Teologi Berita Hidup, 2023)
There are many prophetic books to be found in the Bible, one of which is the book of Jonah. Jonah was sent by God to deliver God's judgment to the wicked city of Nineveh.Â From Jonah chapter 3, it is known that Jonah's short message instilled the Ninevites' trust in God. Previous studies on Jonah 3:1-10 have emphasized God's mercy that cancelled the punishment, and compared Nineveh's repentance with Israel's stubbornness. Using hermeneutical methods to understand the context of historical and theological narratives, this study presents a different focus, which is an exploration of the Ninevites' trust in God. The author investigates the Ninevites' belief in God and explores the meanings and implications of the beliefs presented in the text of Jonah 3:1-10. I then relate this to the broader narrative context of the Book of Jonah and compare it to elements of Old Testament theology. The results show that Jonah 3:5 is the culmination of the Ninevites' repentance that reflects their deep trust in God. The verse describes how the people of Nineveh, both adults and children, responded to the call to repentance by fasting and wearing sack. This reflected a deep change of heart and a willingness to repent collectively, from the king to the commoners. This belief was key to the restoration of the city. The implication of this study is that everyone has the opportunity to turn to God through repentance and receive forgiveness.